Penggunaan Persamaan Diferensial Dalam Pertumbuhan Tanaman - Laia, Erniaman; Bawamenewi, Putri Harta; Hia, Apriani (Jurnal Ilmu Pertanian dan Perikanan, 2024)
The use of differential equations in plant growth is an effective mathematical approach to describe and model the dynamics of plant growth. Differential equations are used to depict changes in plant size and biomass over time, considering factors such as water availability, light, temperature, and nutrients. These models help in predicting agricultural yields, gaining deeper insights into plant physiological processes, and optimizing cultivation practices. By utilizing differential equations, researchers can develop more accurate plant growth models, which are useful in natural resource management and increasing agricultural productivity